EVALUASI PPh FINAL PASAL 4 AYAT 2 ATAS USAHA JASA PELAKSANA KONSTRUKSI - Miki Indika (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The aim of this study is to see final income tax article 4 verse 2 on construction service enterprise in PT Innevo Karya Andesindo Lubuk Linggau. This is descriptive qualittive study. Based on the result of this study, the calculation of final income tax article 4 verse 2 on construction service enterprise in PT Karya Andesindo Lubuk Linggau is not appropriated with government regulation mumber 40 of 2009 and financial minister regulation number 153/PMK-03/2009. At this case this company uses 3% tariff while the regulation states only 2% as small enterpise by multiplying tax value with based tariff (DPP) from construction Service enterprise. The submission of final income tax article 4 verse 2 On Construction service enterprise in PT Innevo Karya Andesindo Lubuk Linggau has been punctual and appropriated with government regulation number 40 of 2009 and financial minister regulation number 153/PMK.03/2009. In submitting financial report PT Innevo Karya Andesindo Lubuk Linggau has been punctual in accordance to government regulation number 40 of 2009 and financial minister regulation number 153/PMK.03/2009 about paid tax.